Advances in Social Science Research Using R - Vinod, Hrishikesh D.; SpringerLink (Online service) (New York, NY : Springer New York, 2010)
This book covers recent advances for quantitative researchers with practical examples from social sciences. The twelve chapters written by distinguished authors cover a wide range of issues--all providing practical tools using the free R software. McCullough: R can be used for reliable statistical computing, whereas most statistical and econometric software cannot. This is illustrated by the effect of abortion on crime. Koenker: Additive models provide a clever compromise between parametric and non-parametric components illustrated by risk factors for Indian malnutrition. Gelman: R graphics in the context of voter participation in US elections. Vinod: New solutions to the old problem of efficient estimation despite autocorrelation and heteroscedasticity among regression errors are proposed and illustrated by the Phillips curve tradeoff between inflation and unemployment. Markus and Gu: New R tools for exploratory data analysis including bubble plots. Vinod, Hsu and Tian: New R tools for portfolio selection borrowed from computer scientists and data-mining experts; relevant to anyone with an investment portfolio. Foster and Kecojevic: Extends the usual analysis of covariance (ANCOVA) illustrated by growth charts for Saudi children. Imai, Keele, Tingley, and Yamamoto: New R tools for solving the age-old scientific problem of assessing the direction and strength of causation. Their job search illustration is of interest during current times of high unemployment. Haupt, Schnurbus, and Tschernig: Consider the choice of functional form for an unknown, potentially nonlinear relationship, explaining a set of new R tools for model visualization and validation. Rindskopf: R methods to fit a multinomial based multivariate analysis of variance (ANOVA) with examples from psychology, sociology, political science, and medicine. Neath: R tools for Bayesian posterior distributions to study increased disease risk in proximity to a hazardous waste site. Numatsi and Rengifo: Explain persistent discrete jumps in financial series subject to misspecification.
Econometric Computing with (3z(BR(3y (B-- Additive Models for Quantile Regression: An Analysis of Risk Factors for Malnutrition in India -- Toward Better R Defaults for Graphics: Example of Voter Turnouts in U.S. Elections -- Superior Estimation and Inference Avoiding Heteroscedasticity and Flawed Pivots: R-example of Inflation Unemployment Trade-off -- Bubble Plots as a Model-Free Graphical Tool for Continuous Variables -- Combinatorial Fusion for Improving Portfolio Performance -- Reference Growth Charts for Saudi Arabian Children and Adolescents -- Causal Mediation Analysis Using R -- Statistical Validation of Functional Form in Multiple Regression Using R -- Fitting Multinomial Models in R: A Program Based on Bock$1 (Bs Multinomial Response Relation Model -- A Bayesian Analysis of Leukemia Incidence Surrounding an Inactive Hazardous Waste Site -- Stochastic Volatility Model with Jumps in Returns and Volatility: An R-Package Implementation.s
Keywords: Statistics; Finance; Economics -- Statistics; Econometrics; Social sciences -- Methodology; Statistics; Statistics for Business/Economics/Mathematical Finance/Insurance.; Econometrics; Environmental Monitoring/Analysis.; Quantitative Finance; Public Health/Gesundheitswesen.; Methodology of the Social Sciences